2001
DOI: 10.1021/ol0155788
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of pH-Dependent Photolysis of Aliphatic Amino Acids and Enantiomeric Enrichment of Racemic Leucine by Circularly Polarized Light

Abstract: It has been proposed that the origin of biological homochirality may be the result of irradiation of a racemic sample of amino acids by circularly polarized light (CPL). To determine the mechanism of enantiomeric enrichment, the irradiation of aliphatic amino acids by CPL was undertaken. An enantiomerically enriched sample (e.g., L isomer enrichment from r-CPL) was found to result from the preferential excitation/decomposition of one enantiomer over another via a Norrish Type II mechanism (leucine, valine, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 15 publications
2
52
0
2
Order By: Relevance
“…Experimentally, Flores et al (1977) produced ee of up to 2.5% by treating leucine with UV CPL irradiation at 212.8 nm, while Nishino et al (2001) obtained similarly low values and further demonstrated a pH dependence for amino acids' decomposition by CPL, which is highest in acidic conditions, i.e., when both carboxyl and amino groups are protonated. In meteorites, the isovaline ee are nearly 20% and this level of asymmetry would seem to refute the suggestion that UV CPL was its sole causation.…”
Section: Circularly Polarized Lightmentioning
confidence: 89%
“…Experimentally, Flores et al (1977) produced ee of up to 2.5% by treating leucine with UV CPL irradiation at 212.8 nm, while Nishino et al (2001) obtained similarly low values and further demonstrated a pH dependence for amino acids' decomposition by CPL, which is highest in acidic conditions, i.e., when both carboxyl and amino groups are protonated. In meteorites, the isovaline ee are nearly 20% and this level of asymmetry would seem to refute the suggestion that UV CPL was its sole causation.…”
Section: Circularly Polarized Lightmentioning
confidence: 89%
“…Inoue et al found that the induced ee-values were dependent on the degree of protonation of leucine's carboxylic group, such that pH values close to 1 generated higher anisotropies. The highest ee value obtained was reported to be close to 0.2% [11,41,49].…”
Section: Anisotropy Spectroscopymentioning
confidence: 88%
“…Further, extensive attempts of inducing higher ee into chiral molecules have been made in strong acidic solutions at (a) different pH values [74,104], (b) the use of two photon excitation processes [105], and (c) with elliptically polarized light [106], yielding enantiomeric excess ee L values of (a, b) 0.2-0.7% and (c) 3%, respectively, for D,L-leucine. All of these experiments were carried out in aqueous solution, where the optical activity of amino acids arises from the (π*, n) electronic transition of the carboxylic group (chromophore) bound to their α-carbon.…”
Section: Asymmetric Photolysis Of Racemic Organic Moleculesmentioning
confidence: 99%